Approaches and methods to assess sedentary behavior in Brazil: a systematic review - Barboza, Luciana Leite Silva (2022)
Our aim was to characterize the Brazilian studies that evaluated sedentary behavior, describing the main characteristics of the studies and identifying the used instruments. Using the PRISMA methodology, the search occurred on 25 August 2019 and was updated on 17 October 2020 in the following databases: PUBMED, LILACS, and SCIELO. Studies in English, Spanish, and Portuguese were included. The inclusion criteria were studies performed with a sample of Brazilians, and that used an instrument to evaluate sedentary behavior. In total, 229 articles were selected. The majority of the studies evaluated children and adolescents. Only 33 studies used device-derived measures and there was a great variability in the questionnaires used. Only 83/198 studies presented quality criteria for the instrument used. Most studies considered the screen time in a typical week plus weekend to characterize sedentary behavior. Therefore, sedentary behavior in Brazil has mostly been evaluated by different questionnaires, and few have been appropriately validated. These findings emphasize the importance of standardization and methodological rigor for assessing sedentary behavior in the Brazilian context.